Contribution of nurse leaders to rural and remote health research in Australia: A non-systematic scoping review. Issue 6 (December 2021) - Beks, Hannah; Walsh, Sandra M.; Binder, Marley J.; Jones, Martin; Versace, Vincent L.
ABSTRACT: Background: Internationally, there is a growing body of literature regarding nurse leadership in health research, including the importance of programs to strengthen nurses in academic leadership roles. Nurse leaders provide a valuable contribution to global health research, influencing policy, clinical practice, and decision-making processes. Nurse leadership is important in rural and remote communities who generally experience poorer health outcomes and barriers to accessing services. Aim: To examine the contribution of nurse leaders to rural and remote health research by reviewing peer-reviewed publication outputs from the Rural Health Multidisciplinary Training (RHMT) program implemented in Australia. Methods: A scoping review framework using non-systematic searching was used. Peer-reviewed publication outputs from the RHMT program database published between 2016 and 2020 were reviewed. Findings were synthesised within the research parameters of the RHMT program. Findings: The RHMT program database contained 1222 unique citations. On title and abstract screening, 796 citations were excluded. Of the 426 citations reviewed for full text, 89 studies were included. Most studies examined the RHMT research parameters of rural health issues (n=24) and rural training strategies (n=22), followed by rural health workforce development (n=21), Aboriginal and Torres Strait Islander health and wellbeing (n=13), and innovative models of care (n=9). Research was largely descriptive, with few studies examining issues specific to the nursing profession (n=21). Discussion: Nurse leaders supported by the RHMT program in Australia provide valuable contributions to rural and remote health research which is not limited to the nursing profession. A paucity of nurse-led innovative models of care were identified. Although included studies were research outputs under the RHMT program, findings are of value to informing future directions of nursing research addressing rural and remote health. Conclusion: Findings provide an overview of the valuable contribution of nurse leaders to rural and remote health research by capturing the interdisciplinary and transdisciplinary nature of nursing research leadership.